PENGARUH GAYA HIDUP TERHADAP ADOPSI PRODUK BERTEKNOLOGI TINGGI PADA KONSUMEN DI INDONESIA - Evi Rinawati Simanjuntak (Journal of Business Strategy and Execution, 2010)
Due to the rapid advancement in technology, high-technology products proliferate faster in terms of variant, functionality and sophistication. Consumer adoption on high-technology product becomes very important to understand. Based on the framework in Technology Adoption Model (TAM), the researcher examines the impact of consumer’s lifestyle toward high-technology product adoption, in the context of Indonesian consumers. The data was collected using survey (online and paper-and-pen) and analyzed using Structural Equation Modeling (SEM). Findings show lifestyle per se does not directly affect customer’s intention to adopt without perceived usefulness. In this research, Internet involvement and e-shopping preference do not contribute to the forming of perceived usefulness of high-technology products; however these two dimensions will affect intention to adopt through perceived ease-of-use. The author provides several managerial implications associated to the above findings.